Chitosan-Coated Solid Lipid Nano-Encapsulation Improves the Therapeutic Antiairway Inflammation Effect of Berberine against COPD in Cigarette Smoke-Exposed Rats. (15th April 2022) - Liu, Hongxiang; Li, Yifan; Zhang, Xiaoying; Shi, Man; Li, Dexu; Wang, Ying
Abstract : Berberine (Ber) is an isoquinoline alkaloid that has shown therapeutic potential in mice with chronic obstructive pulmonary disease (COPD). However, the therapeutic efficiency of Ber is restricted by its low aqueous solubility and bioavailability. Chitosan and solid lipid nanoparticles (SLNs) have demonstrated great abilities as delivery systems in enhancing the bioavailability of therapeutic compounds. The present study aimed to get together the biological features of SLNs with the advantages of chitosan to formulate an efficient nano-carrier platform for the oral delivery of Ber and evaluate the therapeutic effect of the prepared Ber-encapsulated nanoparticles on airway inflammation in cigarette smoke (CS)-induced COPD rats. The Ber-encapsulated SLE-chitosan formulation was manufactured using a modified solvent-injection method followed by a homogenization process. Physicochemical properties, encapsulation efficiency, in vitro stability and Ber release, and pharmacokinetics of the manufactured formulation were evaluated. The COPD rat model was developed by exposing animals to CS. To study the therapeutic efficiency of Ber-encapsulated SLE-chitosan nanoparticles and pure berberine, the histopathological changes of the lung tissues, levels of inflammatory cells and cytokines, and activities of myeloperoxidase (MPO) and superoxide dismutase (SOD) enzymes were evaluated in bronchoalveolar lavage fluid (BALF). Ber-encapsulated SLE-chitosan showed the particle size in nano-range with high stability and controlled slow-release profile in vitro in simulated gastric (pH 1.5) and intestinal (pH 6.8) fluids. Administration of Ber-loaded SLE-chitosan nanoparticles could significantly ameliorate inflammation scores in lung tissues and reduce levels of inflammatory cells (neutrophils and macrophages) and inflammatory cytokines (IL-1 β, Il-6, Il-17, and TNF α ) in BALF when compared with the pure Ber. SLE-chitosan-based nanoparticles can strongly improve the therapeutic anti-inflammatory impact of Ber against CS-induced airway inflammation in COPD rats, suggesting the promising application of Ber-encapsulated SLN-chitosan nanoparticles for treating COPD and other inflammation-mediated diseases.